Peran Komite Sekolah Dalam Meningkatkan Mutu Sarana dan Prasarana Sekolah - Ramadhani, Shafira Nurma (Pedagogi: Jurnal Pendidikan Dasar, 2023)
The purpose of writing this article is that the writer wants to discuss the role of the school committee in improving the quality of school facilities and infrastructure. Completion of school facilities and infrastructure should be the responsibility of the government. One of the parties that has contributed to the improvement of facilities and infrastructure is the school committee, this is in line with one of its duties, which is to help improve the implementation of teaching and learning activities in schools, both in terms of facilities, infrastructure and education. The method used in this journal is SLR (Systematic Literature Review). The results of the analysis of the 9 literature articles that have been reviewed are that in improving the quality of facilities and infrastructure the school committee acts as a deliberative body, supporting body and controlling body.